Labour Market Institutions and Wage Inequality - Winfried Koeniger; Marco Leonardi; Luca Nunziata (Institute for the Study of Labor (IZA), 2004)
In this paper we investigate the importance of labor market institutions such as unemployment insurance, unions, firing regulation and minimum wages for the evolution of wage inequality across countries. We derive a simple log-linear equation of the wage differential as a function of the institutional parameters, total factor productivity, final good prices and relative skill supply. Our estimates for 11 OECD countries imply that labor market institutions can account for a large part of the change of wage inequality across countries after controlling for time and country effects.
Keywords: E24; J65; J51; J31; 330; labor market institutions; wage differential by skill; bilateral monopoly; country panel data; Lohnstruktur; Arbeitsmarktflexibilisierung; Arbeitsmarktpolitik; Schätzung; OECD-Staaten